THEORETICAL FOUNDATIONS FOR IMPROVING TECHNOLOGIES OF SPIRITUAL AND LEGAL EDUCATION OF STUDENTS - Sh.K.Makhmudov (European Science Publishing, 2024)
This article scientifically substantiates the issue of providing spiritual and moral education to young people. The role of spiritual and legal education of youth in human life and the tasks set by the state are also shown.
Keywords: dynamics, legal education, innovation, motive, ability, development, legal culture, legal consciousness.